MTQ Sebagai Upaya Pelestarian Budaya Religius di Nagari Situmbuk - Prima Yoselina; Septiana Arosi’ah; Faishol Arif; Zahwa Ratu Shita; Aura Putri Rinova; Helen Herlinawati (CV. ITTC INDONESIA, 2025)
The preservation of religious culture amidst the increasingly modern era faces significant challenges, as many religious values and traditions are beginning to fade, especially in rural areas of Minangkabau. One of the activities that has persisted and continues to be preserved is Musabaqah Tilawatil Qur’an (MTQ), or the Qur’anic recitation competition. In Situmbuk Village, Salimpaung District, Tanah Datar Regency, MTQ is not only seen as a competitive event, but also as a way for the community to maintain and pass on Islamic traditions that have been inherited for generations. Through MTQ, the village community strives to instill a love for the Qur’an among children and teenagers. Participants are not only taught how to recite correctly and beautifully, but also encouraged to understand the meaning of the sacred verses and apply them in their daily lives. Furthermore, MTQ becomes a moment of togetherness that strengthens relationships among residents, fosters unity, and builds a spirit of mutual cooperation in organizing the event. This research was conducted by students of Universitas Negeri Padang (UNP) as part of the 2025 Community Service Program (KKN). During the program, students were actively involved in various MTQ-related activities, from training participants and assisting the organizing committee to documenting the events. Their involvement not only provided valuable experience but also helped strengthen the relationship between the university and the local community. Observations revealed that MTQ in Situmbuk serves three major functions, as a platform for religious development, a medium for social bonding, and a means of preserving local Islamic culture. Beyond the competition itself, the event is enlivened by a parade, Islamic poetry performances, and distinct local traditions embedded in its execution. Through MTQ, the people of Situmbuk demonstrate that Islamic traditions, rich in values, can survive—and even flourish—when supported by the active participation of the entire community, especially the younger generation. Activities like this must continue to be encouraged so that religious culture remains a living tradition, not merely a memory of the past.